2012
DOI: 10.1016/j.jfa.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Variational principles for topological entropies of subsets

Abstract: Let (X, T ) be a topological dynamical system. We define the measure-theoretical lower and upper entropies h μ (T ), h μ (T ) for any μ ∈ M(X), where M(X) denotes the collection of all Borel probability measures on X. For any non-empty compact subset K of X, we show thatwhere h B top (T , K) denotes the Bowen topological entropy of K, and h P top (T , K) the packing topological entropy of K. Furthermore, when h top (T ) < ∞, the first equality remains valid when K is replaced by any analytic subset of X. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 26 publications
2
97
0
1
Order By: Relevance
“…In 1983 Brin and Katok [8] gave a topological version of the Shannon-McMillan-Breiman theorem with a local decomposition of the measure-theoretical entropy. Recently, Feng and Huang [9] gave a certain variational relation between Bowen's topological entropy and measure-theoretic entropy for arbitrary non-invariant compact set. i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1983 Brin and Katok [8] gave a topological version of the Shannon-McMillan-Breiman theorem with a local decomposition of the measure-theoretical entropy. Recently, Feng and Huang [9] gave a certain variational relation between Bowen's topological entropy and measure-theoretic entropy for arbitrary non-invariant compact set. i.e.…”
mentioning
confidence: 99%
“…where K is any non-empty compact subset of (X, T ), h μ (T ) is the measure-theoretical lower entropy of Borel probability measure μ (see [8,9]). The name slow entropy was introduced into dynamical systems by Katok and Thouvenot [10], Hochman [11] for Z k -actions.…”
mentioning
confidence: 99%
“…Recently, Feng and Huang [16] defined several topological entropies of subsets Z in a topological dynamical system (X, T ). In particular, they defined the upper capacity topological entropy h [16]. If Z is T -invariant and compact, then they are coincident.…”
Section: ) Xmentioning
confidence: 99%
“…Inspired by the approach of defining of the topological entropy of non-compact subset, Feng and Huang [10] introduced the notion of packing entropy in dynamical systems, which resembles packing dimension. An understanding of both the topological entropy and the packing entropy of a set provides the basis for substantially better understanding of the underlying dynamical behavior of the set.…”
Section: Introductionmentioning
confidence: 99%
“…Barreira and Schmeling [13] have showed that BS dimension is the unique root of topological pressure function. Inspired by Pesin [12] and Feng and Huang [10], Wang and Chen [14] generalized it to packing topological pressure. In [14], Wang and Chen also introduced packing version of BS dimension and called it BSP dimension.…”
Section: Introductionmentioning
confidence: 99%